2007
DOI: 10.1038/nbt1304
|View full text |Cite
|
Sign up to set email alerts
|

Towards zoomable multidimensional maps of the cell

Abstract: The detailed structure of molecular networks, including their dependence on conditions and time, are now routinely assayed by various experimental techniques. Visualization is a vital aid in integrating and interpreting such data. We describe emerging approaches for representing and visualizing systems data and for achieving semantic zooming, or changes in information density concordant with scale. A central challenge is to move beyond the display of a static network to visualizations of networks as a function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 59 publications
0
84
0
Order By: Relevance
“…It has been suggested that modules in biological networks follow a hierarchical organizational scheme [13], [21]. However, most modularization algorithms, including dMoNet, are concerned primarily with identifying functional modules that lie at a low level in this hierarchy for the purpose of generating immediately useful and more easily testable hypotheses.…”
Section: F Framing the Comparison To MCL Resultsmentioning
confidence: 99%
“…It has been suggested that modules in biological networks follow a hierarchical organizational scheme [13], [21]. However, most modularization algorithms, including dMoNet, are concerned primarily with identifying functional modules that lie at a low level in this hierarchy for the purpose of generating immediately useful and more easily testable hypotheses.…”
Section: F Framing the Comparison To MCL Resultsmentioning
confidence: 99%
“…A compound node either represents a single entity (e.g., a protein Compound graphs have been used to represent simple signaling pathways [41]. They are also useful to represent the compositions of protein complexes and the connections between their components (if any) [58]. However, they have a number of disadvantages, as follows.…”
Section: Compound Graphsmentioning
confidence: 99%
“…A child node can be either a simple node or a metanode. The edges in E describe different types of relationships between two nodes in V , for e.g., physical interaction, reaction, or sharing of member nodes [58]. Thus, a metagraph can be considered as an extension of a compound graph which does not enforce the 'decomposition tree condition' upon its nodes.…”
Section: Metagraphsmentioning
confidence: 99%
See 2 more Smart Citations